Analysis of the Role of Human Resources in the Implementation of Digitalization of Group Health Insurance Business Processes at PT KLM Insurance - Franciska Natalia; Sitti Rakhman (Paspama Institute, 2025)
Digital transformation in the insurance sector requires not only system renewal but also the readiness of human resources (HR) as the main driver of change. This study aims to analyze the role and preparedness of HR in supporting the digitalization of group health insurance business processes at PT KLM Insurance. Using a qualitative case study approach, data were collected through in-depth interviews with staff and management across key divisions. Findings reveal that digital competencies—both technical skills and soft skills such as adaptability and collaboration—are crucial for successful digitalization. However, challenges such as generational digital gaps, insufficient contextual training, and transitional workload hinder progress. Employee perceptions also show varied attitudes toward digitalization, highlighting the need for inclusive change management strategies rooted in a digital organizational culture. In conclusion, digital transformation success depends not only on technology but also on the full readiness and engagement of HR.